2016
DOI: 10.1007/s00277-016-2700-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection in autologous stem cell transplant recipients in the era of rituximab

Abstract: The incidence of cytomegalovirus (CMV) reactivation/disease after autologous stem cell transplant (ASCT) is much lower than that after allogeneic stem cell transplantation. With the recent use of rituximab during cancer chemotherapy or conditioning regimens prior to transplantation, there has been an increasing concern of opportunistic infections including CMV. In the present study, we reviewed the patients undergoing ASCT from December 2007 to December 2013 to identify those developing CMV reactivation/diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
(22 reference statements)
2
15
0
Order By: Relevance
“…Moreover, the overall analysis of these data does not clearly indicate a significant increase of CMV reactivation rate during the past 20 years, suggesting that the use of novel and more potent therapeutic agents has had only a modest impact on CMV infection/reactivation and overt disease. In fact, the reported increase of CMV infection/reactivation occurrence in lymphoma patients undergoing ASCT after treatment with Rituximab needs further confirmation . On the contrary, the evidence about the impact of Bortezomib in myeloma patients is more persuasive, and these data need to be confirmed by larger prospective studies.…”
Section: Cytomegalovirus Infection In Autologous Hematopoietic Stem Cmentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, the overall analysis of these data does not clearly indicate a significant increase of CMV reactivation rate during the past 20 years, suggesting that the use of novel and more potent therapeutic agents has had only a modest impact on CMV infection/reactivation and overt disease. In fact, the reported increase of CMV infection/reactivation occurrence in lymphoma patients undergoing ASCT after treatment with Rituximab needs further confirmation . On the contrary, the evidence about the impact of Bortezomib in myeloma patients is more persuasive, and these data need to be confirmed by larger prospective studies.…”
Section: Cytomegalovirus Infection In Autologous Hematopoietic Stem Cmentioning
confidence: 91%
“…Nevertheless, even though CMV reactivation still represents an important complication, most cases are successfully managed with a specific antiviral treatment (often administered within outpatient clinical settings). Still, though rare, CMV end‐organ disease remains a serious life‐threatening event in autografted patients, with an incidence up to 4% as reported throughout the last 20 years, although it is showing a trend toward a significant improvement when considering the more recent studies . Of note, overt CMV disease incidence and mortality appear similar irrespective to the diagnostic strategy adopted, further suggesting the limited usefulness of a prospective monitoring of CMV infection .…”
Section: Cytomegalovirus Infection In Autologous Hematopoietic Stem Cmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] showed that the use of rituximab for stem cell transplantation was not associated with an increased risk of CMV reactivation. However, in a small cohort of AAV patients in the Rituximab versus Cyclophosphamide in ANCA-associated Vasculitis (RITUXIVAS) trial there were two cases of CMV infections [40].…”
Section: Significant Infections Associated With Rituximab Therapymentioning
confidence: 99%
“…The incidence of these infections is lower following autologous relative to allogeneic HSCT (43,44). Nevertheless, viral reactivation following autolo-gous stem cell transplant is a significant problem that is facilitated by the loss of T cell function.…”
Section: Discussionmentioning
confidence: 99%